Development of ERP System for Outsourcing Company using Internet of Things and Blockchain Technology - Muhammad Agus Zainuddin; Sritrusta Sukaridhoto; Oktafian Sultan Hakim; Agus Prayudi (JUITA: Jurnal Informatika, 2024)
Enterprise Resource Planning (ERP) systems are pivotal in optimizing operations within outsourcing industries, providing a unified platform for managing business processes. However, the current generation of ERP platforms exhibits significant limitations in seamlessly integrating with emerging technologies such as the Internet of Things (IoT) and blockchain. the paper highlights the transformative potential of effective integration with IoT can offer real-time visibility and operational efficiency such as attendance of the worker, while blockchain can provide robust security and transparency of worker activity through smart contracts. The implementation of an ERP system compared to the traditional manual method to quantify the efficiency gained through this technological advancement. In this analysis, we collected attendance data for 20 employees, documenting the time taken for both manual and ERP-based attendance in seconds. The result of ERP system significantly reduces attendance time. Efficiency is calculated as the percentage reduction in time achieved by using the ERP system compared to the manual method. An average efficiency of 69.05% shows that, overall, the use of ERP is nearly 70% more efficient than the manual method with IoT data transfer using MQTT to blockchain result is 100% retention rate.